Optical properties of surface enhanced Raman scattering - Mattei, G.; Aqida, S.N. (Elsevier, 2024)
The presented chapter is on rapid solidification in materials processing, including metallic glasses of different forms such as flakes, ribbons, wire, droplets, sheets, and bulk. The resulting properties of supercooled alloys are enhanced tensile/compressive strength, yield strain, toughness, Young’s modulus, fracture strength, corrosion resistance, and magnetic properties. The formation of bulk metallic glass (BMG) alloys depends on the base alloy and its multi-component system. Thus, adding metalloids, simple metals, transition metals, and rare earth elements can enhance glass-forming ability with greater maximum thickness, especially in Fe-based BMG alloys. The feasibility of the rapid casting techniques was discussed, along with the examples of BMG alloys produced.